Studies of the root activity in common acid lime (Citrus aurantifolia) using 32P - Báez, María Elena; Delgado, Conrado; Miranda, Diego; Obando, Roberto (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
Since the root system is responsible for water and nutrient absorption from the soil, the objective of this research was to determine the root activity of five-year old plants of common acid lime on ‘Common Lime’ rootstock using isotope 32P as a tracer. In Flandes, Tolima, Colombia (28ºC mean temperature, 68% relative humidity, 1.177 mm annual precipitation, and sandy-loam soil), the application of 32P on three soil depths (15, 30, and 45 cm) and distances from the stem (100, 150, and 200 cm) were evaluated. The isotopic solution was applied at a rate of 5 mL to the zone of the tree disc. The experimental unit was one tree, and a standard sampling technique was used for leaves, branches (stem), and fruits with a 15 day sampling interval and a total of six samples. The isotope activity in the samples was determined by a counter of liquid sparkle using the Cerenkov method. The highest root activity appeared in the first 15 cm and between 15-30 cm of soil depth, reaching values between 14.5 and 18%. The distance where the highest percentage of activity was found, lay at 100 to 150 cm from the stem. The structure of the plant, where the greatest detection of the isotope was achieved, was the leaf. This information indicates that, for five-year old trees of common acid lime, the most active roots are located in the first 30 cm of soil, and between 100 and 150 cm from the stem. Therefore, it is in this zone where fertilizers and water should be supplied and multiple cultures may not be located.